Colossal thermoelectric power in Gd-Sr manganites - Sagar, S.; Ganesan, V.; Joy, Pattayil Alias; Thomas, Senoy; Liebig, A.; Albrecht, M.; Anantharaman, Maliemadom R. (EPL, 2010)
Manganites belonging to the series Gd(1-x)Sr(x)MnO(3) (x=0.3, 0.4 and 0.5) were prepared by wet solid-state reaction and their thermoelectric power was evaluated. Thermoelectric power measurements revealed a peak value at similar to 40 K. All the samples exhibited a colossal thermopower at similar to 40K and in that Gd(0.5)Sr(0.5)MnO(3) exhibited a maximum value of similar to 35 V/K, which is the largest reported for these class of materials at this temperature. Temperature-dependent magnetisation measurements showed that the samples exhibit a phase transition from paramagnetic to spin-glass-like state at these temperatures. Plausible mechanisms responsible for the observed colossal thermoelectric power in Gd-Sr manganites are discussed. Copyright (C) EPLA, 2010